2008
DOI: 10.1159/000124340
|View full text |Cite
|
Sign up to set email alerts
|

Papillon-Lefèvre Syndrome and Malignant Melanoma

Abstract: Papillon-Lefèvre syndrome (PLS) is a rare autosomal-recessive genodermatosis characterized by palmoplantar hyperkeratosis and severe early-onset periodontitis. The development of malignant cutaneous neoplasms within the hyperkeratotic lesions of the syndrome is quite rare. Here, we report on a 51-year-old Japanese woman with PLS associated with recurrent malignant melanoma (MM). Mutation analysis of the cathepsin C gene revealed that the proband was homozygous for a missense mutation, c.415G→A, which is predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Some patients may also be predisposed to pyodermas, and sometimes severe and even fatal internal abscesses may occur [22]. It has also been found that Japanese PLS patients are predisposed to develop melanoma at sites of hyperkeratosis [1]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients may also be predisposed to pyodermas, and sometimes severe and even fatal internal abscesses may occur [22]. It has also been found that Japanese PLS patients are predisposed to develop melanoma at sites of hyperkeratosis [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin C (CTSC), also known as dipeptidyl aminopeptidase I, is a lysosomal proteinase of the papain type that functions in removing dipeptides from the amino terminus of its substrates [1,2]. It is chemically composed of 4 identical units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, severe infections such as liver abscesses or pneumonia occur [2,7]. Recently, a high incidence of malignant melanoma development has been reported in Japanese PLS patients [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Variation in the clinical presentation of PLS has been observed [11-13]. Malignant cutaneous neoplasms arising in the hyperkeratotic skin of PLS patients are very rare [14,15]. To date, an association between Papillon-Lefevre syndrome and two cases of malignant melanoma has been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%